Utilization of Pediatric Psychology Services in Outpatient Pediatric Gastroenterology Within a Rural Health System. Issue 1 (27th May 2022) - Winnick, Joel B.; Focht, Dean R.; Sukumar, Kritika; Kuhn, Benjamin R.; Muldowney, Ryan; O'Dell, Sean M.
Abstract : Increased utilization of pediatric psychology services has been demonstrated following integration into urban pediatric gastroenterology clinics; however, examination within rural health systems is lacking. Utilization of pediatric psychology services was assessed through a retrospective analysis of Electronic Health Record data contrasting referrals occurring six months pre- and post-integration of pediatric psychology in an outpatient pediatric gastroenterology clinic within a rural setting. Significant increases in the number of referrals to pediatric psychology and number of billed initial visits were observed after integration, as was a significant decrease in time to be seen. Patients with public insurance were 3.1 times more likely to complete a billed initial visit compared with patients with nonpublic insurance. The current findings support the integration of pediatric psychology within rural outpatient pediatric gastroenterology clinics to increase utilization and allow more traditionally underserved families to benefit from these services.